History of bacterial meningitis in Cuba: From 19th to 21st centuries - María del Carmen Batlle Almodóvar; Félix Orlando Dickinson Meneses (Universidad de Ciencias Médicas de La Habana, 2019)
Introduction: Bacterial meningitis remains an important health problem worldwide. In Cuba, there are limited research studies about this issue from a historical perspective. Objective: To describe the behavior of this disease in Cuba (19th - 21st   centuries). Material and Methods: A descriptive historical study was carried out between the ends of 1800-2017, using the historical-logical method and a deductive-inductive analysis of multiple bibliographical sources. Development: The first reference to bacterial meningitis in Cuba was made in 1877. The probable introduction of the disease by the US occupation army in 1899 is also considered. In 1901, the meningococci of Weichselbaum was isolated from cerebrospinal fluid, which was probably it first report in Cuba. At the beginning of the 20th century, isolated cases and outbreaks were reported until 1976, when the biggest and larger invasive meningococcal disease began (serogroups C, B). Vaccination against serogroup C started in 1979. In 1980, a special epidemiological surveillance was implemented. The Cuban vaccine VA-MENGOC-BC® against the disease was developed in 1984, which was massively used in 1987. The vaccine contributed to the control of the disease and was included in the National Immunization Program in 1991. Haemophilus Influenzae became the main causative bacterial agent of meningitis until 1999, when the implementation of massive vaccination (Vaxem-Hib® and QuimiHib®) controlled disease. Up to the present, its ecological niche is occupied by pneumococci. Conclusions: From the end of the 19th century to the second half of the 20th century, bacterial meningitis in Cuba behaved as isolated cases and outbreaks. Effective preventive strategies were implemented during and after a huge epidemic, including Cuban vaccines against the disease, that pass on its behavior to a very low endemic disease up to the moment. Key words: Cerebrospinal meningitis, bacterial meningitis, community-acquired bacterial meningitis, meningococcus, pneumococcus, Haemophilus influenzae, vaccines, history.